2019
DOI: 10.1530/vb-19-0013
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-mediated apoptosis and autophagy in ischemic heart diseases

Abstract: Acute myocardial infarction (MI) and its consequences are the most common and lethal heart syndromes worldwide and represent a significant health problem. Following MI, apoptosis has been generally seen as the major contributor of the cardiomyocyte fate and of the resultant myocardial remodeling. However, in recent years, it has been discovered that, following MI, cardiomyocytes could activate autophagy in an attempt to protect themselves against ischemic stress and to preserve cardiac function. Although initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…As mentioned above, HMGB1 acts as a damage-associated molecular pattern which is released either from necrotic cells or by secretion from activated immune cells, hepatocytes, enterocytes, and possibly several other types of cells under distress[ 107 ]. Stress conditions that promote HMGB1 secretion include hypoxia[ 108 ], lethal irradiation[ 109 ], treatment with specific antitumor drugs[ 110 ] or through regulation of autophagy[ 111 ]. HMGB1-induced cell migration requires both IκB kinase (IKK)-β and IKKα-dependent nuclear factor-κB (NF-κB) activation.…”
Section: Hmgb1-sdf1-cxcr4 Axis In Facilitating Tissue-specific Migratmentioning
confidence: 99%
“…As mentioned above, HMGB1 acts as a damage-associated molecular pattern which is released either from necrotic cells or by secretion from activated immune cells, hepatocytes, enterocytes, and possibly several other types of cells under distress[ 107 ]. Stress conditions that promote HMGB1 secretion include hypoxia[ 108 ], lethal irradiation[ 109 ], treatment with specific antitumor drugs[ 110 ] or through regulation of autophagy[ 111 ]. HMGB1-induced cell migration requires both IκB kinase (IKK)-β and IKKα-dependent nuclear factor-κB (NF-κB) activation.…”
Section: Hmgb1-sdf1-cxcr4 Axis In Facilitating Tissue-specific Migratmentioning
confidence: 99%
“…It seems that autophagy is a cytoprotective mechanism against cell death. Nevertheless, autophagy might also become harmful and promote cell death under specific conditions [ 27 ]. The role of autophagy in DOX-induced myocardial injury has been widely debated.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al found that HMGB1 was involved in DOX-induced cardiomyocyte apoptosis and cardiac insufficiency, and inhibiting HMGB1 could alleviate DOX-induced cardiomyopathy [ 20 ]. In addition, HMGB1 could directly interact with Beclin1 and ATG5 and block their calpain-mediated cleavage during inflammation, thereby maintaining proautophagic functions [ 27 ]. In this study, we demonstrated that the expression of HMGB1 was increased after DOX treatment, while the level of HMGB1 was reduced with miR-204 supplementation in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…There is a mutual regulation where one's inhibition affects the release of the other (Zhang et al, 2017), while uncontrolled autophagy increases the HMGB1 release (Tang et al, 2010b;Kim et al, 2020). HMGB1 is crucial for normal autophagy functioning (Tang et al, 2010a;Foglio et al, 2019). As a transcriptional co-factor, HMGB1 regulates the expression of heat shock protein β-1 (Tang et al, 2011;Foglio et al, 2019), which sustains dynamic intracellular trafficking during autophagy.…”
Section: Hmgb1 Autophagy and Mets: A Suggestive Triangulationmentioning
confidence: 99%